Small Farm Food Safety, Fresh Produce: Part 1: Introduction to the PACE Principles - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS)
FCS8842, a factsheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, introduces readers to the PACE principles (prevention, accountability, control, and education) of food safety as they apply to small farm management. Includes a slide presentation. Published by the UF Department of Family, Youth and Community Sciences, October 2007.